Dinamika Keagamaan Masyarakat Perbatasan Paloh, Kabupaten Sambas, Kalimantan Barat - Aslan Aslan; Suhari Suhari; Antoni Antoni; M. Ali Mauludin; Galuh Nashrulloh Kartika MR (Universitas Andalas, 2020)
Paloh is an unseen tribe in the City of Truth or a place where Bunians are believed to have supernatural powers up to now from Kalimantan and its surroundings. The purpose of this study is to describe the Paloh community's belief in the existence of the City of Truth inhabited by subtle people, which isinvisible to the presence of the City of Truth. However, in the eyes of the mind, Paloh is a city for magical creatures that are more beautiful, majestic, luxurious, complete facilities and infrastructure compared to West Kalimantan. To obtain the required data, a series of Paloh community interviews, field observations and documentation have been successfully carried out. The results of this study include that the Paloh people who are still thick with sacred values believe that the Paloh area is the City of Truth. So that the Paloh community still applies restrictions and prohibitions that cannot be violated by anyone who comes to the Paloh forest. If there are people who violate restrictions and prohibitions, then they will receive the consequences in the form of illness, mental disorders such as crazy, stress and even to death. Therefore, Paloh is called the Truth Person, because if they come there with no good intentions, they will be warned by the Bunian people. On this basis, so that now Paloh is still known as the City of Prohibition for those who are intended to do wrong and evil.